Automation for Genomics, Part One: Preparation for Sequencing - Meldrum, Deirdre (Genome Research, 2000)
In the past four years, automation for genomics has enabled a 43-fold increase in the total finished human genomic sequence in the world. This two-part noncomprehensive review will provide an overview of different types of automation equipment used in genome sequencing. Part One focuses on equipment involved in DNA preparation, DNA sequencing reactions, and other automated procedures for preparing DNA for running on sequencers or subsequent analysis; it also includes information on the development of these machines at various genome centers. Part Two, to be published in the next issue, will cover sequencing machinery and array technology, and conclude with a look at the future technologies that will revolutionize molecular biology. “Alternate” sequencing technologies (including mass spectrometry, biochips, and single-molecule analysis) will also be examined.